Normative Power in the European Neighbourhood Policy - Adamčíková, Leona; Maslowski, Nicolas, 1972-; Durrmeyer, Sébastien; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2012)
This Master's Thesis examines whether, and how the normative power of the EU has worked in the European Neighbourhood Policy and its previous forms of cooperation. Beginning with an analysis of theoretical approaches dealing with EU's identity and mainly with the normative power identity developed by Ian Manners and accomplished by Nathalie Tocci, the thesis moves on to an empirical analysis of the ENP and the preceding relations of the EU with its neighbours. Following Ian Manners' tripartite analytical method based on assessment of goals and means applied by a particular foreign policy actor and the impact of its actions, the EU's foreign policy towards its closest neighbours is being examined from the normative power perspective.
Vedoucí práce: Nicolas Maslowski
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international and diplomatic studies [obor dipl. práce]; diplomové práce; master's theses